The Impact of Training and Teaching Experience on Instructor Professionalism at Jayapura Aviation Polytechnic - Jemi Victor Palpialy; Fatmawati Sabur; Musri Kona (Journal of Innovation in Educational and Cultural Research, 2025)
The quality of education is assessed based on the condition of educational institutions, which should be well-maintained and meet all requirements, along with the various components involved in the educational process. This study aims to determine the influence of training, further education, and teaching experience on improving the professionalism of productive instructors at Jayapura Aviation Polytechnic. The purposive sampling method is used to obtain 40 productive instructors as respondents based on ex-post facto research, and the data analysis is conducted through the Statistical Product and Service Solution (SPSS) program. The results show that training, further education, and teaching experience significantly influence the professionalism of educators/instructors/lecturers at Jayapura Aviation Polytechnic. Educators/instructors/lecturers with adequate teaching experience and participation in sufficient training will help realize national education goals and establish quality standards.